A Retrospective Comparison Study between the Effectiveness and Safety of Fixed Dose Combination of Vildagliptin versus Sitagliptin with Metformin in Type 2 Diabetes Mellitus Patients - Samuel, Ndayishimye; Rodrigues, Prudence A. (Indian Journal of Pharmacy Practice)
Aim: To compare the effectiveness and safety of fixed dose combination of vildagliptin 50mg versus sitagliptin 50mg with metformin 500mg in Type 2 Diabetes Mellitus patients. Method: Retrospectively 160 subjects were divided into two groups: A and B, in group A 80 subjects received a fixed dose combination of sitagliptin 50mg with metformin 500mg and 80 subjects in group B received a fixed dose combination of vildagliptin 50mg with metformin 500mg for a period of 24 weeks. Glycated hemoglobin, fasting plasma glucose, postprandial glucose, bodyweight, potassium, microalbuminurea and creatinine were evaluated as outcomes parameters while safety was evaluated by reporting adverse event including hypoglycemic effect. Results: Both groups have shown a greater reduction in plasma glucose parameter: glycated hemoglobin reduced up to 0.97% (P<0.000) for vildagliptin group versus 0.928% (P<0.000) in sitagliptin group, fasting plasma glucose reduced up to 27.46mg/dl (P<0.000) in vildagliptin group versus 20.925mg/dl (P<0.019) for sitagliptin and postprandial glucose reduced up to 42.25mg/dl (P<0.000) for vildagliptin versus 35.260mg/dl (P<0.000) for sitagliptin. There were no significant alteration in kidney parameters in both groups: potassium, creatinine, micro albuminurea, body weight was increased by one l kilogram (1.02kg) in sitagliptin group whereas it was reduced by 0.47kg in vildagliptin group. The incidence of hypoglycemic effect were comparable less in both group 6.25% in vildagliptin group versus 5% in sitagliptin group other adverse drug reactions GIT was mild in both group did not require any alteration or discontinuation of the drugs. Conclusion: Both drugs are effective and safe in the management of type 2 diabetes mellitus. These drugs improve plasma glucose and are safe from hypoglycemic effect and they are not associated with the increase of body weight. However, vildagliptin offer a superior benefit over sitagliptin in the management of type 2 diabetes mellitus
Keywords: Type 2 Diabetes Mellitus; Sitagliptin; Vildagliptin; Metformin.